Perlindungan Hukum bagi Anak yang Berhadapan dengan Hukum: Studi Kasus pada Tindak Pidana Seksual di Kota Palembang - Hendra, Hendra (Disiplin : Majalah Civitas Akademika Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2025)
This research focuses on legal protection for children involved in legal processes, particularly in cases of sexual offenses. The study examines the regulations governing child protection within the Indonesian criminal justice system and how this legal protection is applied in cases of sexual crimes. The author will identify various issues and barriers in providing adequate protection for children through literature review and case studies. Additionally, recommendations for improvements to the existing legal system will be provided. To gain a better understanding of this issue, this research uses a qualitative approach with case studies.